Contributions to the Phenomenology of Heightened Reality - Losoncz, Mark (Problemos, 2023)
This article analyzes the experience of heightened reality, whereby subjects feel or think that what they are facing is reality itself, or somehow a ‘more real reality’, a hyperreality. My main examples for this specific kind of metacognitive supervision are from reports about the near-death experience, the psychedelic experience and the mystical experience. I will interpret accounts of such experiences using first of all philosophical phenomenology and theories of sense of reality. I criticize and try to complement Martin Fortier’s model of the plural taxonomy of sense of reality. In addition, I propose a triadic model of the experience of reality and, based on the analysis of the testimonies of heightened reality, I have developed a triadic model, according to which one dimension of reality experience is merely heightened reality, the other two being self-evident immersion in reality and the irruptive suspension of ordinary experience.